An analysis of urban resilience in selected communities in Kumasi and its environs - Darkwah, Rhoda Mensah (2016)
Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in Partial Fulfilment of the Requirements of Master of Science Development Planning and Management, 2016